PROPOSED IMPROVEMENTS TO THE DECLINE IN PRODUCTIVITY LEVEL OF MICROBIOLOGY LABORATORIES USING THE OMAX AND 5W+1H METHODS AT PT. PFI - farij nick faldo (Baut Dan Manufaktur, 2023)
Measuring the level of productivity is carried out to improve productivity in the future so that it becomes better by considering all the factors needed. This research was conducted with the aim of analyzing the level of productivity in the microbiology laboratory and the causes of the decreased level of productivity because the quality department received several complaints from the site team leader of other departments regarding delays in product releases. To measure the level of productivity, several categories were observed, including the lead time analysis (the amount of time required from the start of the analysis process until the analysis is completed), the amount of work time, and the number of task schedules (scheduling work done every day). The method used is the Objective Matrix (OMAX) and followed by fishbone diagrams and 5W + 1H. The results of this study obtained the level of productivity during the measurement period from January to December 2022, which has an average score above 600 and tends to fluctuate. The highest occurred in February with a score of 951 and the second highest occurred in June with a score of 882, while the lowest productivity occurred in April with a score of 198. The highest increase in productivity occurred in February with a productivity index of 58% and the highest decrease in productivity occurred in April with a productivity index of -67% which was caused by, among other things, human error, work waiting time, and reagents running out and not being available. Therefore, suggestions for improvements such as determining capacity planning, evaluating in scheduling with other departments, providing a monthly stock monitoring schedule and making work schedules can be made by discussing with the team beforehand.